2016
DOI: 10.1128/aem.03939-15
|View full text |Cite
|
Sign up to set email alerts
|

An Outer Membrane Protein Involved in the Uptake of Glucose Is Essential for Cytophaga hutchinsonii Cellulose Utilization

Abstract: bCytophaga hutchinsonii specializes in cellulose digestion by employing a collection of novel cell-associated proteins. Here, we identified a novel gene locus, CHU_1276, that is essential for C. hutchinsonii cellulose utilization. Disruption of CHU_1276 in C. hutchinsonii resulted in complete deficiency in cellulose degradation, as well as compromised assimilation of cellobiose or glucose at a low concentration. Further analysis showed that CHU_1276 was an outer membrane protein that could be induced by cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 29 publications
(42 reference statements)
0
24
0
Order By: Relevance
“…The proteins of unknown function encoded by genes near cel5B, cel9C, and cel9D are likely candidates, and the genetic tools available allow this to be tested. Several genes near cel9C have recently been demonstrated to be important for cellulose utilization, although their exact functions are not known (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…The proteins of unknown function encoded by genes near cel5B, cel9C, and cel9D are likely candidates, and the genetic tools available allow this to be tested. Several genes near cel9C have recently been demonstrated to be important for cellulose utilization, although their exact functions are not known (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…C. hutchinsonii appears to use a contact-dependent digestion strategy to utilize cellulose (23); however, details of the mechanism are still a mystery. Recently, several proteins have been found that play important roles in cellulose degradation by C. hutchinsonii, such as the outer membrane proteins CHU_1276 (24) and CHU_1277 (22), the periplasmic protein CHU_2981 (25), and the protein CHU_0170 (26), which is a component of the type IX secretion system. Zhu et al found that two periplasmic endoglucanases were required for use of crystalline cellulose as a sole carbon and energy source (20).…”
mentioning
confidence: 99%
“…Specifically, a significant number of genes which had been involved in glycan biosynthesis and carbohydrate metabolism were discovered to be downregulated within the category of metabolism (62/148). Given that the integrity of the outer membrane protein profile has been found to be critical for cellulose utilization by C. hutchinsonii and given that outer membrane deficiency is often seen in mutant strains which have defects in cellulose utilization (20)(21)(22)(23)27), we observed that a further nine genes which encode putative outer membrane proteins that had unclassified functions were independently grouped within the regulon (see Fig. 7 and Data Set S3).…”
Section: Figmentioning
confidence: 97%
“…Among others, outer membrane proteins which might directly contact cellulose substrate or its digested hydrolysate are considered to play key roles in the utilization of cellulose by C. hutchinsonii (20). Specifically, mutations of genes predicted to encode hypothetical outer membrane proteins, including the genes CHU_1276, CHU_1277, CHU_1719, and CHU_3220, have been reported to lead to defective cellulose assimilation (21)(22)(23)(24). Moreover, a selection of other genes that are involved in the cellulose utilization of C. hutchinsonii have been identified by either random transposon mutagenesis or targeted mutagenesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation